Cooperative Design in Marketing of NPP Location Territories as a Factor of Social and Economic Security - Rudenko, V. A.; Golovko, M. V.; Agapova, S. P.; Rogacheva, J. S.; Tkachev, V. G.; Antsibor, A. V.; Setrakov, A. N. (Глобальная ядерная безопасность, 2022)
The article discusses some problems of providing the socio-economic security of the territories where nuclear facilities are located using the example of Volgodonsk, their dynamics are presented. The authors present the starting results of the project work of the initiative community of the city focused on the improvement of the territory. The importance of adhering to the principles of marketing, collaborative design, and tactical urbanism in the development of territorial development strategies is noted. Target and motivational guidelines for all groups of stakeholders are defined. The tasks and main directions of complicity in the project are set. The role of the key partner and project expert, the Agency for Strategic Initiatives, is outlined.